PENYELESAIAN SENGKETA PEMUTUSAN HUBUNGAN KERJA (STUDI PUTUSAN NOMOR : 259/PDT. SUS-PHI/2021/PN.MDN): Settlement of Termination of Employment Disputes (Study of Decision Number: 259/PDT. SUS-PHI 2021/PN.MDN - Nikita Syaharani; Yogo Pamungkas (AMICUS CURIAE, 2024)
Termination of Employment (PHK) by an employer is termination of employment whose initiative comes from the employer, due to violations or mistakes committed by workers/labourers due to other factors, such as downsizing employees, closing companies that are losing money, changes in status, and so on. Minutes of bipartite or tripartite negotiations are an absolute requirement for pursuing a dispute at the Industrial Relations Court. The conclusions chosen by the author are conclusions drawn from the point of view of deductive logic. The conclusion of the research is based on a case study of the Decision of the Industrial Relations Court at the Medan District Court Special Class IA number 259/Pdt. Sus-PHI/2021/PN.Mdn: First the Panel of Judges was of the opinion that bipartite and tripartite negotiations had been carried out but these negotiations failed or no agreement was reached, so that the exception of the Defendants stating that the case was aquo which had never been carried out in bipartite negotiations was rejected by the judge. Second, the Judge did not consider the provisions on the remaining unpaid wages/salaries. This has been regulated in Article 61 A of Law Number 13 of 2003 jo. Article 15 Paragraph of Government Regulation Number 35 of 202 which requires employers to pay compensation money to workers whose work relationship is based on PKWT